Co-Infection of HBV in Partially/Non-Vaccinated Diagnosed HCV Positive Patients (Medical Forum Monthly, 2024)
Objective: To determine the frequency of co-infection of HBV in partially/non-vaccinated diagnosed HCV positive patients.Study Design: Descriptive / cross-sectional study.Place and Duration of Study: This study was conducted at the Department of Medicine, DHQ Teaching Hospital Bannu, Khyber Pakhtunkhwa from Feb 2015 to Aug 2015.Materials and Methods: Data was collected from 371 patients already diagnosed as HCV positive for more than 1 year, through a preset questionnaire, to note their vaccination status against HBV. Those patients who were partially or non-vaccinated, were screened for HBsAg by ELISA, to document the co-infection.Results: Out of 371 HCV positive patients, 201 patients were males (54.2%) and 170 (45.8%) were females. Only 89 (23.99%) patients were vaccinated (49 males and 40 females) while the rest 282 were either non-vaccinated (260 patients) or partially vaccinated (22 patients). So overall 282 (76.01%) HCV positive patients were lacking proper vaccination against HBV, and merely 89 (23.99%) patients were properly vaccinated against HBV. Out of those 282 HCV positive patients, who were either non-vaccinated or partially vaccinated, 14 (4.96%) patients were found to be HBsAg positive by ELISA (co-infection).Conclusion: The frequency of vaccination against HBV was very low in this high risk adult group patients (18-60 years) already infected with HCV. Only 89 (23.99%) patients were properly vaccinated, which is an alarming situation. Out of these 282 HCV positive patients lacking proper vaccination against HBV, 14 (4.96%) patients were found to be HBsAg positive by ELISA (co-infection). This co-infection can be prevented by proper planing by health care provider to improve vaccination.